2019
DOI: 10.1002/jbm.b.34316
|View full text |Cite
|
Sign up to set email alerts
|

Degradation behaviors and cytocompatibility of Mg/β‐tricalcium phosphate composites produced by spark plasma sintering

Abstract: Magnesium (Mg)‐based materials have shown great potentials for bioresorbable implant applications. Previous studies showed that Mg with 10 and 20 vol % β‐tricalcium phosphate (β‐TCP) composites produced by spark plasma sintering, improved mechanical properties when compared with pure Mg. The objectives of this study were to evaluate the degradation behaviors of Mg/10% β‐TCP and Mg/20% β‐TCP composites in revised stimulated body fluid (rSBF), and to determine their cytocompatibility with bone marrow derived mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…The results demonstrated that HA effectively reinforced the mechanical properties and improved corrosion resistance of the fabricated composite compared to those of the AZ91 alloy [9]. Narita et al fabricated Mg/β-TCP composites via the spark plasma sintering method for biodegradable material applications [10]. The findings indicated that the in vitro corrosion resistance and cytocompatibility of the fabricated Mg/β-TCP composites have been enhanced effectively compared to those of pure Mg.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that HA effectively reinforced the mechanical properties and improved corrosion resistance of the fabricated composite compared to those of the AZ91 alloy [9]. Narita et al fabricated Mg/β-TCP composites via the spark plasma sintering method for biodegradable material applications [10]. The findings indicated that the in vitro corrosion resistance and cytocompatibility of the fabricated Mg/β-TCP composites have been enhanced effectively compared to those of pure Mg.…”
Section: Introductionmentioning
confidence: 99%
“…The total area of RPs in the Mg/20% β-TCP was larger than that in the Mg/10% β-TCP. Figure 1D,E show scanning electron microscope (SEM) images and the corresponding energy dispersive spectroscopy (EDS) analysis (reproduced from our previous study [34]). The results show that Ca was diffused to the adjacent area of the Mg matrix to the RPs area.…”
Section: Resultsmentioning
confidence: 95%
“…The results show that Ca was diffused to the adjacent area of the Mg matrix to the RPs area. The detection of carbon was attributed to adventitious carbon contamination and diffusion from a carbon die used in the SPS process [34]. The formed RPs were characterized by XRD as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations